2005
DOI: 10.1074/jbc.m412238200
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Context Effects on Oligo(dT) Termination Signal Recognition by Saccharomyces cerevisiae RNA Polymerase III

Abstract: Eukaryotic RNA polymerase (Pol) III terminates transcription at short runs of T residues in the coding DNA strand. By genomic analysis, we found that T 5 and T 4 are the shortest Pol III termination signals in yeasts and mammals, respectively, and that, at variance with yeast, oligo(dT) terminators longer than T 5 are very rare in mammals. In Saccharomyces cerevisiae, the strength of T 5 as a terminator was found to be largely influenced by both the upstream and the downstream sequence context. In particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 57 publications
1
113
1
Order By: Relevance
“…RNAPIII recycling is also dependent on a natural termination signal (Dieci and Sentenac 1996;Ferrari et al 2004). Termination can be influenced by sequences surrounding the T tract (Bogenhagen and Brown 1981;Mazabraud et al 1987;Gunnery et al 1999;Braglia et al 2005). Braglia et al (2005) proposed that the surrounding residues and, in particular, downstream residues of the yeast terminator influence the pausing time or the processivity of RNA-PIII.…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 99%
See 2 more Smart Citations
“…RNAPIII recycling is also dependent on a natural termination signal (Dieci and Sentenac 1996;Ferrari et al 2004). Termination can be influenced by sequences surrounding the T tract (Bogenhagen and Brown 1981;Mazabraud et al 1987;Gunnery et al 1999;Braglia et al 2005). Braglia et al (2005) proposed that the surrounding residues and, in particular, downstream residues of the yeast terminator influence the pausing time or the processivity of RNA-PIII.…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 99%
“…In yeast, the most frequent T stretch length is six or seven with no stretch shorter than five Ts (Allison and Hall 1985;Hamada et al 2000). In mammals, a stretch of four Ts is the most frequent terminator, and a stretch of more than five Ts is rare (Braglia et al 2005). RNAPIII pauses not only at the terminator region but also at several other T stretches during transcription (Campbell and Setzer 1992;Matsuzaki et al 1994).…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 99%
See 1 more Smart Citation
“…A curious feature of the transcription unit is the presence of a run of 6 consecutive T residues located a few bp downstream of the box A. Even though the T 6 sequence is a strong termination signal for Pol III, we have recently shown that it behaves as an unusually weak terminator in the SNR52 context (33). The T 6 element might be relevant for SNR52 expression, because it is also present in this position in the genomes of at least two other Saccharomyces species (S. paradoxus and S. mikatae).…”
Section: Resultsmentioning
confidence: 99%
“…In Vitro Transcription Assays-Transcription of class III genes was reconstituted in vitro essentially as described (15,33). All reactions contained 0.6 g of TFIIIC partially purified up to the DEAE Sephadex A-25 step (34), except that yeast nuclear extract (35) was used as a starting material; 40 ng of recombinant TBP and 80 ng of recombinant Brf1, both purified from overexpressing Escherichia coli cells (34); and 10 ng of highly purified RNA polymerase III (15).…”
Section: Methodsmentioning
confidence: 99%